Road Traffic Noise Levels at Different Types of Residential Areas in Nibong Tebal, Penang - Halim, Herni (International Journal of Integrated Engineering, 2019)
Traffic vehicles on the road networks during their movement create noise that has greater impact on environment. The sources, the receivers and the place of transition, where the sound wave propagates, are the three vital parameters for the field of noise acoustics. For this research, the aim of this study is to assess traffic noise levels between different types of residential areas in Nibong Tebal, Penang. The study is carried out in order to achieve the following three main objectives, which are to assess the level of traffic noise at selected residential areas, to characterize the traffic flow composition nearby study areas, and to compare noise levels between low density and terraced house residential areas. The noise levels measurements were carried out periodically in the morning (from 0700 to 1100), evening (from 1600 to 1900), and at night (from 2200 to 2300) for 15 minutes using a sound level meter. The traffic characteristics were measured simultaneously during noise levels measurements. The highest equivalent continuous noise levelsfor the low density residential areas was at Kampung Batu 2 in the evening with 65.9 dB(A), while for the medium density residential areas, Taman Sri Acheh contributed 68.60 dB(A) during the morning. The lowest equivalent continuous noise levelswere obtained at Kampung Simpang Tiga in the morning that contributed 54.9 dB(A) for low density residential areas. However, the minimum equivalent continuous noise levelsobtained for the medium density residential areas was at Taman Ilmu Indah in the morning with 63.10 dB(A). The results obtained, clearly show that the equivalent continuous noise level for all study sites exceeded the maximum permissible sound level for medium density areas during daytime (from 7.00 am to 10.00 pm), which is 55 dB(A), while at night time (from 10.00 pm to 7.00 am) Â is 45 dB(A), and for low density residential areas during daytime (from 7.00 am to 10.00 pm) is 55 dB(A), while at night time (from 10.00 pm to 7.00 am)Â  is 45 dB(A), respectively. These values are based on the guidelines for environmental noise limits and control by the Department of Environment, Malaysia.